Argyrophilic nucleolar organizer regions of thyroid lesions on fi ne needle aspiration smears - Chalise, S; Thapa, S; Sayami, G; Shrestha, A (Journal of Pathology of Nepal, 2013)
Background: Argyrophilic nucleolar organizer region is higher in malignant nuclei as compared to reactive and benign nuclei. The main objective of this study was to evaluate the role of Argyrophilic nucleolar organizer region and its extent in differentiating benign and malignant lesions, particularly with respect to follicular neoplasms of the thyroid. Materials and Methods: This was a prospective, cross sectional study which included 110 patients presenting with thyroid swelling. The fi ne needle aspiration smears were studied by conventional methods and silver staining for Argyrophilic nucleolar organizer region. In 50 cases, diagnosis was confi rmed by histopathology. The Argyrophilic nucleolar organizer region count was done and the mean Argyrophilic nucleolar organizer region count per nucleus was calculated along with pattern of distribution. Results: Mean Argyrophilic nucleolar organizer region count was higher in neoplastic as compared to non-neoplastic and infl ammatory lesions. Papillary carcinoma had the highest mean Argyrophilic nucleolar organizer region count (5.40 ± 0.86) and the lowest count was seen in Hashimoto’s thyroiditis (2.10 ± 0.36). Higher mean Argyrophilic nucleolar organizer region count was recorded in follicular carcinoma (4.84 ± 1.42) as compared to follicular adenoma (3.5 ± 0.27) which was found to be statistically signifi cant (P